Human Gastric Mucins Differently Regulate Helicobacter pylori Proliferation, Gene Expression and Interactions with Host Cells - Skoog, Emma C. (Public Library of Science, 2012)
Helicobacter pylori colonizes the mucus niche of the gastric mucosa and is a risk factor for gastritis, ulcers and cancer. The main components of the mucus layer are heavily glycosylated mucins, to which H. pylori can adhere. Mucin glycosylation differs between individuals and changes during disease. Here we have examined the H. pylori response to purified mucins from a range of tumor and normal human gastric tissue samples. Our results demonstrate that mucins from different individuals differ in how they modulate both proliferation and gene expression of H. pylori. The mucin effect on proliferation varied significantly between samples, and ranged from stimulatory to inhibitory, depending on the type of mucins and the ability of the mucins to bind to H. pylori. Tumor-derived mucins and mucins from the surface mucosa had potential to stimulate proliferation, while gland-derived mucins tended to inhibit proliferation and mucins from healthy uninfected individuals showed little effect. Artificial glycoconjugates containing H. pylori ligands also modulated H. pylori proliferation, albeit to a lesser degree than human mucins. Expression of genes important for the pathogenicity of H. pylori (babA, sabA, cagA, flaA and ureA) appeared co-regulated in response to mucins. The addition of mucins to co-cultures of H. pylori and gastric epithelial cells protected the viability of the cells and modulated the cytokine production in a manner that differed between individuals, was partially dependent of adhesion of H. pylori to the gastric cells, but also revealed that other mucin factors in addition to adhesion are important for H. pylori-induced host signaling. The combined data reveal host-specific effects on proliferation, gene expression and virulence of H. pylori due to the gastric mucin environment, demonstrating a dynamic interplay between the bacterium and its host.